2002
DOI: 10.1007/s11746-002-0484-8
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic acids of borage (Borago officinalis L.) and evening primrose (Oenothera biennis L.)

Abstract: The composition of phenolic acids, both free and liberated from esters and glycosides, was determined in evening primrose and borage seeds by GC and MS. The free phenolic acid fraction was predominant in these seeds. Protocatechuic acid was the principal phenolic acid of the free and esterified phenolic acids in evening primrose seeds. Ferulic acid represented a high proportion of the free phenolic acids, but hydroxycaffeic acid was the major constituent of phenolic acids liberated from esters of borage seeds.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
1
23
1
1
Order By: Relevance
“…The total contents of free phenolics found in berries were similar to those reported by Zadernowski et al (18) for defatted borage and evening primrose seeds, but over 10 times lower than those found in defatted rapeseed meals (24). Eleven free phenolic acids were tentatively identified in this fraction ( Table 2).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The total contents of free phenolics found in berries were similar to those reported by Zadernowski et al (18) for defatted borage and evening primrose seeds, but over 10 times lower than those found in defatted rapeseed meals (24). Eleven free phenolic acids were tentatively identified in this fraction ( Table 2).…”
Section: Resultssupporting
confidence: 86%
“…(Table 1). These values are up to 30 times higher than those reported for defatted evening primrose and borage seeds (18), as well as sesame and cottonseed flours …”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…More recent studies have suggested that the antioxidant properties of evening primrose may arise from phenolic acids such as gallic, caffeic, p-hydroxybenzoic, vanillic, ferulic and salicylic acids, as well as proanthocyanidins and flavanols (Zadernowski, Nowak-Polakowska, & Konopka, 1996), catechin and epicatechin derivatives or protocatechuic and gallic acids and esters (Peschel, Dieckmann, Sonnenschein, & Plescher, 2007;Schmidt, Niklová, Pokorný, Farkaš, & Sekretár, 2003). Salicylic,vanillic,gallic, ferulic and caffeic acids are found in smaller quantities in evening primrose seeds (Zadernowski, Naczk, & Nowak-Polakowska, 2002).…”
Section: Evening Primrosementioning
confidence: 99%
“…A large number of flavonoids have been found in Oenothera sp., including myricetin, quercetin and kaempferol glycosides, as well as a biflavonoid of mirycetin, namely speciin [Howard et al, 1972;Zinsmeister et al, 1977;Marzouk et al, 2009]. The phenolic acids present in these species are mainly gallic acid together with ethyl-and metyl-esters, protocatechuic, caffeic and ellagic [Zinsmeister & Bartl, 1971;Zadernowski et al, 2002;Schmidt et al, 2003]. Fractionation of the seed extracts, obtained from defatted pulp, showed the presence of hydrolysable and condensed tannins.…”
Section: Introductionmentioning
confidence: 99%